Carbon and Electron Flow in Clostridium cellulolyticum Grown in Chemostat Culture on Synthetic Medium - Guedon, E. (American Society for Microbiology, 1999)
Previous results indicated poor sugar consumption and early inhibition of metabolism and growth when Clostridium cellulolyticum was cultured on medium containing cellobiose and yeast extract. Changing from complex medium to a synthetic medium had a strong effect on (i) the specific cellobiose consumption, which was increased threefold; and (ii) the electron flow, since the NADH/NAD(+) ratios ranged from 0.29 to 2.08 on synthetic medium whereas ratios as high as 42 to 57 on complex medium were observed. These data indicate a better control of the carbon flow on mineral salts medium than on complex medium. By continuous culture, it was shown that the electron flow from glycolysis was balanced by the production of hydrogen gas, ethanol, and lactate. At low levels of carbon flow, pyruvate was preferentially cleaved to acetate and ethanol, enabling the bacteria to maximize ATP formation. A high catabolic rate led to pyruvate overflow and to increased ethanol and lactate production. In vitro, glyceraldehyde-3-phosphate dehydrogenase, lactate dehydrogenase, and ethanol dehydrogenase levels were higher under conditions giving higher in vivo specific production rates. Redox balance is essentially maintained by NADH-ferredoxin reductase-hydrogenase at low levels of carbon flow and by ethanol dehydrogenase and lactate dehydrogenase at high levels of carbon flow. The same maximum growth rate (0.150 h(−1)) was found in both mineral salts and complex media, proving that the uptake of nutrients or the generation of biosynthetic precursors occurred faster than their utilization. On synthetic medium, cellobiose carbon was converted into cell mass and catabolized to produce ATP, while on complex medium, it served mainly as an energy supply and, if present in excess, led to an accumulation of intracellular metabolites as demonstrated for NADH. Cells grown on synthetic medium and at high levels of carbon flow were able to induce regulatory responses such as the production of ethanol and lactate dehydrogenase.